2018
DOI: 10.1002/mgg3.410
|View full text |Cite
|
Sign up to set email alerts
|

The Genomic Consultation Service: A clinical service designed to improve patient selection for genome‐wide sequencing in British Columbia

Abstract: BackgroundAccess to clinical diagnostic genome‐wide sequencing (GWS; exome or whole genome sequencing) is limited in British Columbia. The establishment of a translational research initiative (CAUSES) to provide diagnostic genome‐wide sequencing for 500 children necessitated the development of a genomic consultation service, a clinical service established to provide consultation for physicians considering GWS for their pediatric patients throughout British Columbia. The Genomic Consultation Service provides pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…We have described our experience of establishing a multi-disciplinary team format for the application of NGS in a clinical setting, using a prospective ES case series to illustrate the operation and results of this approach. Our findings demonstrate the value of a multidisciplinary evaluation and consensus-based decision-making by a team within a clinical environment, complementing and informing related but distinct experience reported elsewhere such as the Genome Clinic Task Force (Geneva) [6], Genomic Consultation Service (British Columbia) [35], Individualised Medicine Clinic (Mayo) [36] and Undiagnosed Disease Network (NIH) [9]. Here we have shown how this approach can be implemented at a local level within a national health service, the impact of case selection, sequencing strategy and evaluation of results, and the health economics of such a format.…”
Section: Discussionsupporting
confidence: 77%
“…We have described our experience of establishing a multi-disciplinary team format for the application of NGS in a clinical setting, using a prospective ES case series to illustrate the operation and results of this approach. Our findings demonstrate the value of a multidisciplinary evaluation and consensus-based decision-making by a team within a clinical environment, complementing and informing related but distinct experience reported elsewhere such as the Genome Clinic Task Force (Geneva) [6], Genomic Consultation Service (British Columbia) [35], Individualised Medicine Clinic (Mayo) [36] and Undiagnosed Disease Network (NIH) [9]. Here we have shown how this approach can be implemented at a local level within a national health service, the impact of case selection, sequencing strategy and evaluation of results, and the health economics of such a format.…”
Section: Discussionsupporting
confidence: 77%
“…Although the population studied was ethnically and geographically diverse, our findings may not be generalizable to other patient groups. Most of the children were over the age of 3 at time of testing, which is relevant because it has been reported that both testing decisions and acceptance of living without a diagnosis may be influenced by child's age (Aldridge et al., 2021; Elliott et al., 2018; Li et al., 2016). The model of care provided in CAUSES, with most negative results being provided by telephone, may also influence parents’ perceptions when interviewed several months afterward.…”
Section: Discussionmentioning
confidence: 99%
“…This study took place in the Children's & Women's Health Centre of BC, Vancouver, Canada, the major referral center and only dedicated pediatric and women's hospital in the Province of British Columbia and the Yukon Territory. We recruited parents from a translational research study, CAUSES (Clinical Assessment of the Utility of Sequencing and Evaluation as a Service) (Elliott et al., 2018), which performed trio‐based GWS (either exome or whole genome sequencing) on 500 pediatric patients and their parents, where the child had a suspected, but undiagnosed genetic disorder. At the time of the CAUSES study, GWS was not available clinically.…”
Section: Methodsmentioning
confidence: 99%
“…The patient cohorts screened for known STR expansions in this study consist of the ES data of 141 trios or quads from the Clinical Assessment of the Utility of Sequencing and Evaluation as a Service (CAUSES) Study [ 25 ] and the WGS data of 160 trios or quads from the Integrated Metabolomics And Genomics In Neurodevelopment (IMAGINE) [ 26 ] or CAUSES Studies. Subjects enrolled in the CAUSES Study were children who were suspected on clinical grounds to have a single gene disorder but in whom conventional testing had not identified a genetic cause.…”
Section: Methodsmentioning
confidence: 99%
“…The PCR-free whole-genome sequencing data of Coriell samples with known short tandem repeat expansions analyzed in the current study can be accessed in the European Genome-phenome Archive repository: https://www.ebi.ac.uk/ega/datasets/EGAD00001003562 [ 10 ]. Individual patient clinical or genomic data from the CAUSES [ 25 ] and IMAGINE [ 26 ] Studies are not available because they are potentially individually identifiable and not consented for public release. Investigators who wish access to the summary data of CAUSES and IMAGINE Studies can contact Dr. Jan Friedman (jmf@bcchr.ca).…”
mentioning
confidence: 99%